Assessment of the scope of ambulatory medical aid for the patients with leiomyoma of the uterus provided in the system of obligatory insurance in St. Petersburg - L. V. Kochorova; B. L. Tsivyan; M. V. Okulov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The investigation was carried out at the bases of Hospital № 40 and of the Health Protection Department of I.P. Pavlov St. Petersburg State Medical University. The authors analyze the scope of the ambulatory medical aid for the patients with leiomyoma of the uterus provided in the system of obligatory medical insurance in St. Petersburg. The scope of the ambulatory aid for the mentioned patients significantly varies in different districts of the city - the fact to be taken into consideration.